Parent involvement begins at birth - Goldberg, Sally, 1947- (Boston : Allyn and Bacon, 1997)
The optimum educational environment. The guidance approach to self-esteem, independence, and a productive life. Education from birth to five. The child-centered activity-based program.
Keywords: Child; Parent; Parenting -- Study and teaching -- United States; Child development -- Study and teaching -- United States; Infants -- Care -- Study and teaching -- United States; Toddlers -- Care -- Study and teaching -- United States